2019
DOI: 10.1155/2019/2098083
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Alleviated Referral Hindpaw Hyperalgesia via Suppressing Spinal Long-Term Potentiation (LTP) in TNBS-Induced Colitis Rats

Abstract: Although referred pain or hypersensitivity has been repeatedly reported in irritable bowel syndrome (IBS) patients and experimental colitis rodents, little is known about the neural mechanisms. Spinal long-term potentiation (LTP) of nociceptive synaptic transmission plays a critical role in the development of somatic hyperalgesia in chronic pain conditions. Herein, we sought to determine whether spinal LTP contributes to the referral hyperalgesia in colitis rats and particularly whether electroacupuncture (EA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…(b)), 40 mmHg (P < 0.01, Figure 1(c)), 60 mmHg (P < 0.01, Figure 1(d)), and 80 mmHg (P < 0.05,Figure 1(e)), indicating that inhibiting activation of astrocyte reduced chronic visceral hypersensitivity in IBS model which is consistent with previous reports on the role of glial cells in other inflammatory visceral hypersensitivities[17].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…(b)), 40 mmHg (P < 0.01, Figure 1(c)), 60 mmHg (P < 0.01, Figure 1(d)), and 80 mmHg (P < 0.05,Figure 1(e)), indicating that inhibiting activation of astrocyte reduced chronic visceral hypersensitivity in IBS model which is consistent with previous reports on the role of glial cells in other inflammatory visceral hypersensitivities[17].…”
supporting
confidence: 91%
“…Intestinal inflammation injury leads to the activation of spinal cord astrocytes which release a large number of neuroactive substances, enhance the sensitivity and reactivity of dorsal horn neurons, and generate central sensitization [15,16]. For example, 2,4,6-trinitrobenzene sulfonic acid (TNBS) can lead to the enhancement of long-term potentiation (LTP) in pain synaptic transmission of the spinal dorsal horn in colitis rats [17]. e purinergic system regulates the activity of the glutamate energy system [18] which affects the NMDA receptor and also plays an important role in the communication of glial cells by regulating glutamate release in glial cells of the spinal cord [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and experimental studies have shown beneficial role of acupuncture and moxibustion in reducing IBD disease activity and inflammation [20][21][22]. Our previous studies also found that both EA and moxibustion have therapeutic effect on colitis rats [4,11,23]. Herein, we sought to observe whether EA and moxibustion could be able to regulate the astrocyte and microglial and mitochondria activation of hippocampal area in the colitis model, providing new clues for studying the curative effect of EA and moxibustion on the basis of gut-brain axis.…”
Section: Introductionmentioning
confidence: 71%
“…Electroacupuncture at ST36 acupoint can effectively inhibit lipopolysaccharide-induced multiple peritonitis in mice [ 47 ]. ST36 was also chosen to investigate the mechanism of moxibustion analgesic effect in our previous studies [ 23 , 48 , 49 ]. Moxibustion at ST36 acupoint can effectively increase the expression of HSP in cardiac muscle, brain tissue, gastric mucosa, and other distal tissues and organs in healthy rats [ 50 ].…”
Section: Discussionmentioning
confidence: 99%